Identification of Types of Fish Caught in Mangrove Ecosystem KampungMadong, KampungBugis Village, Tanjung Pinang City, Riau Islands Province - Lusi Noviyanti; Eddiwan Eddiwan; Efawani Efawani (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACTMangrove ecosistem in Kampung Madong is inhabited by numerous aquatic organism, including fish. This study aims to determine the types of fish caught in themangrove ecosystem of KampungMadong. This research was conducted in March-April 2019. The method used in the research was survei method on three sampling area observation with four sampling in a month. The analyzed include morphology, morphometrics and meristik of fishes.Water quality parameters measurd were temperature was 29,5-30,5oC, pH was 7,4-7,5, salinity was 32,5-34,5o/oo and dissolved oxygen was 62-6,4mg/L. The identification of fish samples using the Saanin identification book (1968), White et al. (2013) and Sulistionoet al. (2015). The result shows that there were 171 fishconsisting of4 ordo, 10 families,11 genus and 13 species of fish,they were: Cephalopholisminiata, Anyperodonleucogrammicus, Schatophagusargus, Siganusvirgatus, Siganusguttatus, Carangoidesmalabaricus, Eubleekeriasplendens, Sphaeramia orbicularis, Anadontostomachacunda,Sardinellafimbriata, Paraplotosusalbilaris, GerresfilamentosusandValamugilspeigleri. Keywords : Morphology, Morphometrics, Meristik, Water quality